Factors associated with tick bites and pathogen prevalence in ticks parasitizing humans in Georgia, USA. Issue 1 (December 2016) - Gleim, Elizabeth; Garrison, Laurel; Vello, Marianne; Savage, Mason; Lopez, Gaylord; Berghaus, Roy; Yabsley, Michael
Abstract Background The incidence and emergence of tick-borne diseases has increased dramatically in the United States during the past 30 years, yet few large-scale epidemiological studies have been performed on individuals bitten by ticks. Epidemiological information, including disease development, may provide valuable information regarding effectiveness of tick bite prevention education, pathogen transmission, human-disease dynamics, and potential implications for under reporting of tick-borne diseases. Methods Ticks found attached to Georgia residents were submitted for identification and polymerase chain reaction (PCR) testing forFrancisella tularensis, Ehrlichia, Anaplasma, Borrelia, andRickettsia spp. Tick bite victims were interviewed three weeks after the tick bite to identify various epidemiologic factors associated with infestation and if signs suggestive of a tick-borne disease had developed. Fisher's exact test of independence was used to evaluate associations between various factors evaluated in the study. A multivariable logistic regression model was used for the prediction of non-specific illness post-tick bite. Results From April 2005-December 2006, 444 participants submitted 597 ticks (426Amblyomma americanum, 142Dermacentor variabilis, 19A. maculatum, 7Ixodes scapularis, 3Amblyomma sp.) which originated from 95 counties. Only 25 (34 %) of 74 interviewed individuals purposely took tick bite prevention measures. Ticks that were PCR positive for bacterial organisms were attached to 136 participants. Of the 77 participants who developed non-specific illness, 50 did not have PCR positive ticks, whereas 27 did have PCR positive tick (s). Of those 27 individuals, 12 fit the criteria for a possible tick-borne illness (i.e., tick attached >6 h [if known], ≥4 day incubation period, and the individual exhibited clinical symptoms typical of a tick-borne illness without exhibiting cough, sore throat, or sinus congestion). Ticks from these individuals were positive forR. amblyommii (n  = 8), E. ewingii (n  = 1 ), R. montana (n  = 1), R. rhiphicephali (n  = 1), andRickettsia sp. TR-39 (n  = 1). Conclusions Although illnesses reported in this study cannot definitively be connected with tick bites, it does provide insight into development, diagnosis, and treatment of possible tick-borne diseases post-tick bite. The study also provided data on pathogen prevalence, and epidemiologic factors associated with tick bites, as well as tick presence by county in Georgia.